1998
DOI: 10.1142/s0218625x98001511
|View full text |Cite
|
Sign up to set email alerts
|

LEEM Studies of Phase Separations and Surface Depletion of Co and Ni on Si(111)

Abstract: Low energy electron microscopy images of Si(111) surfaces during submonolayer deposition of Co or Ni at temperatures near 700 • C reveal a phase separation into a disordered "ring cluster" phase and the ordered 7 × 7 reconstruction. For Co/Si(111) we find that temperature-driven phase separations at a fixed dose are reversible and occur at a fixed surface coverage. The shape of the phase boundary reveals a repulsive interaction between Co-containing ring clusters in the disordered phase. For Ni/Si (111), disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…19 -R23.4°, and (1 × 1)-ring cluster (RC) phases. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] These surface silicides are thought to be intermediate states before the formation of thick epitaxial silicides. It has been reported that ´n 2 and 2 2-R45°phases form on a Si(100) substrate depending on the Ni coverages and substrate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…19 -R23.4°, and (1 × 1)-ring cluster (RC) phases. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] These surface silicides are thought to be intermediate states before the formation of thick epitaxial silicides. It has been reported that ´n 2 and 2 2-R45°phases form on a Si(100) substrate depending on the Ni coverages and substrate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The Ni-Si interface is a typical example of a system in which appear a number of surface phases during reactive diffusion. The initial stages of nucleation and growth of 2D and 3D phases at the Ni/Si interface have been extensively studied by structural or microscopy surface techniques, such as low-energy electron diffraction (LEED), low-energy electron microscopy (LEEM), scanning tunnelling microscopy (STM) [9][10][11][12]. Several 2D phases are reported to appear during the reaction of an ultrathin Ni film with a Si (111) substrate, ( phases [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These RCs might well be thought of as surface molecules of silicide, since they exist as discrete units in which the bonding resembles crystalline silicide. Recent experiments using the high temperature in situ imaging capability of low energy electron microscopy (LEEM) have explored the kinetic properties of these RCs in terms of 2D phase transitions, surface diffusion and assimilation into true silicide structures [61][62][63][64][65].…”
Section: Surface Structuresmentioning
confidence: 99%